2007
DOI: 10.1590/s1677-55382007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of oxidative stress and sperm chromatin damage in male infertility: an evidence based analysis

Abstract: Oxidative stress (OS) in the reproductive tract is now a real entity and concern due to the potential harmful effects of high levels of reactive oxygen species (ROS) on sperm number, motility, quality, and function including damage to sperm nuclear DNA. Evaluation of OS related damage to non-functional sperm is highly relevant as intracytoplasmic sperm injection (ICSI) technique, an effective therapy for severe male factor infertility, bypasses the majority of reproductive tract deficiencies. Despite the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(169 citation statements)
references
References 126 publications
(129 reference statements)
0
151
0
18
Order By: Relevance
“…Some authors have reported a positive correlation between ROS production and sperm DNA damage 18,19 . The results of our study demonstrated that there was a trend of rising DFI %, from control group to NSI group to infertile group with abnormal semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported a positive correlation between ROS production and sperm DNA damage 18,19 . The results of our study demonstrated that there was a trend of rising DFI %, from control group to NSI group to infertile group with abnormal semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic metabolism of human sperm produces various reactive oxygen species (ROS), which are potentially harmful to the sperm plasma membrane with its high content of polyunsaturated fatty acids (1)(2)(3). There is growing evidence that lipid peroxida�lini�al Urology �lini�al Urology tion damage to the plasma membrane of spermatozoa plays an important role in the mechanism of male infertility (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…We can predict that the injection of these compromised spermatozoa may affect the outcome of assisted reproduction in multiple ways, including effects on the fertilization rates, embryo cleavage, and pregnancy rates. In addition, our data show that high level of seminal TGFß1 (>100 ng/ml) which is a critical semen parameter associated with infertility, is a predictive factor for an increased risk of sperm DNA damage [14][15][16][17].…”
Section: Resultsmentioning
confidence: 66%
“…Subjects currently on any medication or antioxidant supplementation were not included [16][17][18][19][20][21][22][23][24]. In addition, subjects with testicular varicocele, genital infection, leukocytespermia, chronic illness and serious systemic diseases, smokers and alcoholic men were excluded from the study because of their well-known high seminal ROS levels and decreased antioxidant activity.…”
Section: Exclusion Criteriamentioning
confidence: 99%